Multiple Functions of Phosphoinositide-3 Kinase Enhancer (PIKE) - Chi Bun Chan; Keqiang Ye (The Scientific World Journal)
GTP-binding proteins are the molecular switches of numerous cellular functions, including migration, proliferation, and differentiation. In the past 10 years, we have characterized a novel class of GTPases called phosphoinositide-3 kinase enhancer (PIKE) that interacts with PI3K/Akt. In neurons, PIKE is involved in the protective mechanisms against neuroexcitotoxic insults by linking various receptors, such as mGluR1 and Unc5H2, to the PI3K cascade. Interestingly, the PIKE gene (CENTG1) is also amplified in a variety of human cancers and enhances Akt activity, leading to their resistance against apoptosis and invasion. It has also been demonstrated that PIKE is involved in endosome formation and nuclear protein accumulation. Thus, PIKE possesses multitudinous biological functions rather than solely acting as an apoptosis inhibitor. In this review, we will update our current knowledge of the role of PIKE in various cellular activities. Moreover, the functions of PIKE in peripheral tissues as revealed by the unique phenotypes in PIKE knock-out mice will be discussed as well.